Sox8: a multifaceted transcription factor in development and disease - González Alvarado, Marıá Nazareth; Aprato, Jessica (Biology Open, 2025)
Sox8 is a transcription factor that belongs to the Sox family of high-mobility-group domain containing proteins and is closely related to Sox9 and Sox10. During prenatal development, Sox8 is expressed in several ectoderm-, endoderm- and mesoderm-derived tissues and has been implicated in processes of organogenesis and differentiation. Sox8 expression is found in several important cells such as Sertoli cells in the male gonad, glial cells, satellite cells, and chondrocytes. However, Sox8 is not essential for the proper development of any of the involved systems, as it functions redundantly with Sox9 or Sox10 and no major developmental disturbances have been noticed in its absence. Despite its perceived limited importance as a developmental regulator, Sox8 exhibits a more significant role in late development and adult tissues. Several studies highlight the importance of Sox8 for the homeostasis of adipose tissue, Sertoli cells and the blood-testis-barrier functioning, and the maintenance of myelin in the central nervous system. Emerging evidence points to SOX8 as a promising candidate for a disease-causing gene in humans and suggests that changes in SOX8 function or expression could contribute to pathological states. For instance, genetic variants of SOX8 have been linked to multiple sclerosis and familial essential tremor, while SOX8 alterations have been related to poor cancer prognosis and infertility. This Review provides an overview of Sox8’s versatile role in development and adult tissues as well as its lesser-known contributions to various diseases, and its potential as a therapeutic target.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Development; Disease; Nervous system; Sex determination; Sox8; Transcription factor